PENDIDIKAN DALAM KELUARGA LANGKAH AWAL PELAKSANAAN PENDIDIKAN SEPANJANG HAYAT - vevi sunarti (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2013)
Lifelong education is very basic stuff to be applied because of our educationtoday face a variety of challenges and problems, including; formal educationare not able to answer the demands of the people to keep and continue tolearn. Population increases very rapidly and at the same time increasingpeople's desire to get an education, which is the cumulative demand and theavailability of adequate educational methods. The development of modernscience requires the basics of a solid education and mastery abilityconstantly, and thus require a longer education in accordance with theconcept of lifelong education. The family as the first and primary containeris expected to provide answers to the needs of lifelong education. Forms ofeducation provided amid the family or as a support for further educationwhich would be obtained by a child, indicating that the family had beenpreparing as early container lifelong education.